PENGARUH PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA PADA SUB SEKTOR PERTAMBANGAN LOGAM DAN MINERAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - MOHD. IDRIS DALIMUNTHE (JURNAL MUTIARA AKUNTANSI, 2018)
Tax is the largest source of revenue for the state, but on the other hand tax is a cost for the company because the tax burden will reduce income, therefore many companies do tax planning to minimize the tax burden and earn more income. Companies in the mining sector have an important role in the Indonesian capital market. Management's ability to determine the quality and quantity of production greatly influences the price and purchasing power of consumers so that it can help companies implement adequate strategies to overcome competition with other companies to achieve maximum profit. This study aims to determine the effect of tax planning on earnings management. The type of data used in this study is quantitative data. The data sources used in this study were obtained from the financial statements of mining and metal mining sub-sector companies listed on the Indonesia Stock Exchange from 2010 to 2015. The results showed a relationship between variables (X), namely tax planning on earnings management (Y) the metal and mineral mining subsector companies listed on the Indonesia Stock Exchange amounted to 1.3% and showed significant relationships between variables. Key Word: Tax Planning, Profit Management, Profit Distribution